Description of a new species of the newt genus Tylototriton sensu lato (Amphibia: Urodela: Salamandridae) from southwestern China - Li, Shi-Ze; Liu, Jing; Shi, Sheng-Chao; Wei, Gang; Wang, Bin (Zootaxa, 2022)
A new species of the genus Tylototriton sensu lato from Tongzi County, Guizhou Province, China was described. Molecular phylogenetic analyses based on mitochondrial 16S and ND2 gene sequences indicated the new species as the most closely related species of T. dabienicus in Henan. The new species could be identified from its congeners by a combination of the following morphological characters: (1) body size medium (TOL 120.5–135.1 mm and SVL 61.1–65.9 mm in males, and TOL 123.5–127.6 mm and SVL 66.7–69.2 mm in females); (2) gular fold present; (3) the tail length shorter than the snout-vent length; (4) the distal ends and ventral surfaces of digits, peripheral area of cloaca, and the lower margin of tail orange; (5) the distal tips of the limbs greatly overlapping when the fore and hind limbs being pressed along the trunk; (6) fingertips reaching to the level beyond the snout when the forelimbs being stretched forward; (7) nodule-like warts on body sides continuous and no obvious. The new species is known only from the montane forests of Huanglian Nature Reserve, Tongzi County, Guizhou Province, China. We recommend the new species to be listed as Critically Endangered.